PENGARUH MODEL PBI (PROBLEM BASED INSTRUCTIONS) DISERTAI MEDIA AUDIOVISUAL TERHADAP KETERAMPILAN PROSES SAINS DAN HASIL BELAJAR SISWA (Materi Momentum dan Impuls Kelas X MAN 1 Jember) - Ika Nur Aini Alfianti; Singgih Bektiarso; Albertus Djoko Lesmono (FKIP Universitas Jember, 2018)
AbstractThe purpose of this research were to study the effect of PBI (Problem BasedInstructions) model with audiovisual media towards the student’s science process skillsand student learning outcomes. This research was an experiment research conducted inMAN 1 Jember. The population in this research were all students of Xth grade in MIAMAN 1 Jember academic year 2016/2017. The data on student’s science process skillsand student learning outcomes were obtained from written tests at the end of momentumand impulse learning in the experiment class and control class. To examine thehypothesis, this research used independent sample t-test with SPSS 23 version.According to the independent sample t-test analysis, the results of this research were asfollows: (1) PBI (Problem Based Instructions) model with audiovisual media has ansignificant effect to science process skill in physics Xth grade in MAN 1 Jember and (2)PBI (Problem Based Instructions) model with audiovisual media has an significanteffect to student learning outcomes in physics Xth grade in MAN 1 Jember.Keyword: PBI (problem based instructions), audiovisual media, student’s scienceprocess skills, student learning outcomes